2016
DOI: 10.1111/ahg.12153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nicotine on HPA Axis Activity in Females is Modulated by the FKBP5 Genotype

Abstract: Tobacco smoking modulates activity in the hypothalamic-pituitary-adrenal (HPA) axis and is used to cope with stress, especially by females. The single nucleotide polymorphism (SNP) rs1360780, linked to FK506-binding protein 51 (FKBP5), has been shown to affect HPA axis functioning, and has thus been suggested as a promising candidate for indicating vulnerability to stress-related disorders. The aim of this study was to investigate the interaction between nicotine consumption and rs1360780 on cortisol plasma le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The distribution of rs1360780 alleles did not deviate from the Hardy-Weinberg equilibrium (χ2 = 0.29, p = .59). As per Grabe et al (2016) and other studies on rs1360780 genotype (Koopmann et al, 2016), we combined the CC and CT carriers into one group, thus comparing T-homozygotes with C allele carriers.…”
Section: Genotypingmentioning
confidence: 99%
“…The distribution of rs1360780 alleles did not deviate from the Hardy-Weinberg equilibrium (χ2 = 0.29, p = .59). As per Grabe et al (2016) and other studies on rs1360780 genotype (Koopmann et al, 2016), we combined the CC and CT carriers into one group, thus comparing T-homozygotes with C allele carriers.…”
Section: Genotypingmentioning
confidence: 99%
“…For example, Rogausch, Kochen, Meineke, and Hennig (2007) found that G allele carriers at rs41423247 of NR3C1 were more likely to become smokers and had significantly higher daily cigarette consumption than C homozygotes. Other SNPs within NR3C2, FKBP5, and CRHR1 have also been examined in relation to smoking outcomes (dos Santos et al, 2012;Jensen et al, 2015;Koopmann et al, 2016;Rovaris et al, 2013;Tang et al, 2015), with mixed results. Interestingly, a small GWAS of daily cigarette use reported associations at SNPs within NR3C2, providing additional evidence that genes underlying HPA-axis function may also play a role in smoking behavior.…”
Section: Do Pleiotropic Effects Underlie Sex-differences In Smokingmentioning
confidence: 99%
“…Several studies have investigated drug use and FKBP5 genetic variability in humans. FKBP5 genotype is associated with the severity of withdrawal from nicotine (Jensen and Sofuoglu, 2016), as well as the effect of nicotine on the HPA axis (Koopmann et al, 2016). The interaction of early life trauma and FKBP5 genetic variation predicts heavy drinking in college students (Lieberman et al, 2016), and FKBP5 genetic variability is associated with severity of alcohol withdrawal (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%